2009
DOI: 10.1073/pnas.0811155106
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious effects of language-specific terminology on preattentive color perception

Abstract: It is now established that native language affects one's perception of the world. However, it is unknown whether this effect is merely driven by conscious, language-based evaluation of the environment or whether it reflects fundamental differences in perceptual processing between individuals speaking different languages. Using brain potentials, we demonstrate that the existence in Greek of 2 color terms-ghalazio and ble-distinguishing light and dark blue leads to greater and faster perceptual discrimination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
369
7
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 312 publications
(420 citation statements)
references
References 17 publications
31
369
7
13
Order By: Relevance
“…Previous research on early ERP evidence of categorical color perception has shown that it varies predictably according to language-specific terminology (25,26) and that it very probably is automatic and preattentive (28). The present study has shown that the categorical modulation of the vMMN by color difference is lateralized to the RVF and so presumably is controlled by the left cerebral hemisphere, where most language functions are housed and where this finding confirms much behavioral (2,(14)(15)(16)(17)19) and neurophysiological (23)(24)(25)(26)28) evidence. Lateralized Whorfian effects on early color processing strongly appear to be automatic and preattentive.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Previous research on early ERP evidence of categorical color perception has shown that it varies predictably according to language-specific terminology (25,26) and that it very probably is automatic and preattentive (28). The present study has shown that the categorical modulation of the vMMN by color difference is lateralized to the RVF and so presumably is controlled by the left cerebral hemisphere, where most language functions are housed and where this finding confirms much behavioral (2,(14)(15)(16)(17)19) and neurophysiological (23)(24)(25)(26)28) evidence. Lateralized Whorfian effects on early color processing strongly appear to be automatic and preattentive.…”
Section: Resultssupporting
confidence: 75%
“…This finding suggests that the use of lexical information in the left hemisphere is the origin of differential visual hemifield responses to color stimuli (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). There has been some suggestion that the left cerebral hemispheric areas implicated in important language functions may serve as a top-down control source that modulates the activity level of the visual cortex (24)(25)(26)(27)(28), but little is known about whether this lateralized effect occurs at early, preattentive perceptual processing stages or at postperceptual decision/response phases. Visual mismatch negativity (vMMN) is widely held to reflect the brain's early and automatic change in event-related potentials (ERPs) in response to a novel stimulus (29)(30)(31).…”
mentioning
confidence: 99%
See 3 more Smart Citations